Pengembangan Sistem Informasi Inventori Barang Berbasis Website Menggunakan Model Rapid - Muhamad Zaki; Adi Saputra; Ahmad Syauqie Syahrizan; Sandi Ocviana; Yulianti Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Within a company, data processing is very important for a company to take place. But many companies do not have good data processing. There are still many things that cause data processing errors. Including in PT. Indojaya Multi works, data processing in this company including poor data processing so that there are still many errors that have occurred. Pt. Indojaya Mukti Karya is one of the companies established in Indonesia that provides goods and serves the implementation of the project that is shiny floor. Therefore, we try to develop data processing in the company to be better and efficient. In order to avoid mistakes that have occurred, for that we develop an Inventory system that has several features such as goods forms, clients, suppliers, warehouses and QR codes. In its application this information system is created using the programming language html, css, java script, php and database. And so this information system aims to minimize data processing errors in the company.